Lettori di libri europei in Inghilterra dopo il Grand Tour - Brundin, Abigail; Roberts, Dunstan (Studi Politici, 2023)
The passage of European books into English great houses following the Grand Tour is a marker of cultural and linguistic exchange that often extended beyond the house itself to other readers and contexts. This article looks at some examples of Italian books in English Great House libraries curated by the National Trust.